The role of social innovation and innovator competencies in the local economic development of disadvantaged settlements - Varga, Krisztina; Veresné Somosi, Mariann; Lipták, Katalin (European Public & Social Innovation Review, 2025)
Introduction: The most disadvantaged settlements in Hungary face several economic and social difficulties and challenges, such as a shrinking and ageing population, the emigration of the working age population, high unemployment, low income generating capacity, and lack of creativity. In these areas, the local economy is also highly deficient and underdeveloped due to limited job opportunities. Social innovation is particularly needed in disadvantaged settlements. Methodology: Due to the specificity of the topic and the special characteristics of the region under study, the participatory action research method was given special attention. Results: the study aims to present a successful good practice from the North-Hungary region, which has tried to provide an innovative solution to a complex social problem. Discussion: Our research also includes an examination of public involvement efforts as a key driver of social innovation, which requires supporting the innovative role of institutional leaders in generating specific social innovation solutions. Conclusions: Mentoring innovators and developing their competencies is essential for the successful implementation of social innovation processes, which can be seen as the cornerstone of local economic development in disadvantaged areas.